Techniques and Practices of Yoruba Wood Carving - Adeyanju, Joel ‘Lade (2014)
This essay discusses some of the basic techniques of traditional wood carving practices among the Yoruba. It attempts to explain why certain carved images are decorated. It also appraises the contributions of Father Kevin Carroll's experimental workshop to the development of wood carving tradition in Nigeria. The study evaluates the styles and themes of traditional carving in general